2015
DOI: 10.1002/ppp.1837
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Freezing Temperatures of Saline Silty Soils

Abstract: The freezing temperature of soil is an important index to judge whether it is in a frozen state or not, and plays a key role in distinguishing salt expansion from frost heave. Freezing experiments on sulfate saline soil and its ion solution indicate that the initial freezing temperature of the soil is mainly determined by the properties of the ion solution. The effects of saline soil types and saline solution concentrations on the freezing temperature are also investigated. An equation to calculate the freezin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 16 publications
(21 reference statements)
1
48
0
Order By: Relevance
“…Ion analysis indicated that sodium, chloride and sulfate were dominant in the dissolved salts [16]. The soil samples were rinsed with distilled water to desalinize them until the electrical conductivity (probe: Hydra probe SDI-2) declined to zero.…”
Section: Methodsmentioning
confidence: 99%
“…Ion analysis indicated that sodium, chloride and sulfate were dominant in the dissolved salts [16]. The soil samples were rinsed with distilled water to desalinize them until the electrical conductivity (probe: Hydra probe SDI-2) declined to zero.…”
Section: Methodsmentioning
confidence: 99%
“…Cooling temperature curve -The cooling temperature curves were obtained by cooling the frozen saline soils with salt contents 0.0%, 0.5%, 1.5%, and 2.5% (the salt is anhydrous Na 2 SO 4 fine particles) from the initial temperature of 10°C. Referring to previous research (Xu et al 2010;Bing and Ma 2011;Wan et al 2015), the freezing temperatures of frozen saline soils can be determined. From the cooling temperature curves (Fig.…”
Section: Influence Of Salt Content On the Shear Strength Of Frozen Samentioning
confidence: 99%
“…Sulfate soil is a predominant and representative type of sulfate saline soil found in western China (Wan et al, 2015), and sodium sulfate is most prevalent in large areas of the Beilu River on the Qinghai-Tibet Plateau. Therefore, sodium sulfate soil was selected to study salt expansion mechanisms.…”
Section: Experimental Designmentioning
confidence: 99%